Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content 1. The impact of change management on the organizational performance of higher education institutions (Applied to Imam Muhammad bin Saud Islamic University) Taghreed Mater Alotaibi 2. The reality of applying servant leadership behaviors in Palestinian universities " An applied study on Al-Aqsa University " Emad Youniss El-Sawalhy, Shaimaa Jamel Abadsa, Yasmeen Sameer Al-Shaer, Shaima Ahmed Meqdad, Abdullah Mohammed Ali Aqel 3. Cultural, Marketing and Personal Factors of Consumer Behavior during Corona pandemic: Perspective of Final Consumer in Unaizah city- KSA Abdulwahab Saleh Alwahashi, Tariq Mohammed Almahi 4. The Iranian position on the Russian-Ukrainian war in 2022 Noura Ali Abdallah 5. The Impact of Investing in Renewable Energy Projects on the Financial Performance of Jordanian Eelectricity Companies since 2017 Bayan Ahmad Alyasein 6. The Economic Policies Impact on the cement industry in Sudan (2018-2005) Ismaeel Ibraheem Omer Saeed, Abdelbagi Sheikheldeen Habeeballah, Abdelrahman Ali Elbashir 7. Climate justice repercussions and implications Sami ElTayeb Idris Mohamed